Estimating woody debris recruitment in a stream caused by a typhoon-induced landslide: a case study of Typhoon Lionrock in Iwaizumi, Iwate prefecture, Japan. Issue 1 (1st January 2018) - Chaithong, Thapthai; Komori, Daisuke; Sukegawa, Yuto; Anzai, Satoshi
Abstract: A landslide can generate large amounts of debris in the form of boulders, cobbles, soil, and wood. The woody debris produced by a landslide flows into a downstream river or village; it can form obstructions in the stream and destroy houses. In this study, we aimed to develop a procedure for estimating woody debris recruitment into streams following a landslide. Understanding the volume of woody debris can help predict and prevent hazards from this debris. The proposed procedure combines a shallow landslide model, tree density data, and observational data following landslide occurrence. The study site is a sub-watershed of the Omoto River watershed in the town of Iwaizumi in Iwate prefecture in Japan; this town was affected by Typhoon Lionrock in 2016. Typhoon Lionrock delivered over 200 mm of rainfall in 24 h and induced many landslides. Based on field surveys, we found that approximately 524 m 3 of woody debris jammed the narrow section under a railway bridge (including voids) and approximately 178 m 3 of woody debris to formed a dam in the stream channel of the target watershed (including voids). Using the proposed protocol, we estimate that woody debris recruitment to the stream was approximately 638 m 3 .